L’utopie de l’internation littéraire - Abdelghani Fennane (Carnets)
“Who still speaks today of THE French literature?” It’s in these problematic words that Abdelkebir Khatibi, an eminent figure of the French-speaking nations – who has just passed away – defined his critical relation with French language and literature in his literary work Figures de l’étranger dans la littérature française (Paris: Denoël, 1987). A book which presents itself, in its political aspect, as a criticism to the literary nationalism and the hope for internationalizing literature the founding fathers of which are a new race of writers called by A. Khatibi: “l’étranger professionnel”. This concerns taking literature (any literature) out of its ethno-centric frame in a way that questions the confrontation of the native with the extra-native, and the centre with periphery. My presentation consists in a clarification of the subversive principle on which this utopia is based by trying to put into evidence the implicit dialogue that A. Khatibi had with the dissident figures of the French literature (Jean Genet, Victor Segalen, Roland Barthes…).